Characterization of polysaccharides from cystocarpic and tetrasporic stages of Sub-Antarctic Iridaea cordata - Barahona, Tamara; Rodriguez Sanchez, Rodrigo A.; Noseda, Miguel D.; Mansilla Muñoz, Andres Omar; Matsuhiro, Betty; Prado, Hector J.; Matulewicz, Maria C. (My University, 2021)
The polysaccharide systems from cystocarpic and tetrasporic phases of the Sub-Antarctic algae Iridaea cordata were studied. Cystocarpic plant polysaccharides are mainly composed by carrageenans of the x-family. However, agaran structures were also detected in the fraction soluble in 2.00 M KCl, after fractionation with increasing potassium chloride solutions. The presence of 13-D-galactose-alpha-L-galactose 3-sulfate, 13-D-galactose-alpha-L-galactose 6sufate, 13-D-galactose 6-sulfate-alpha-L-galactose 6-sufate, and of 13-D-galactose 4-sulfate-alpha-L-galactose 2,3-disulfate diads was confirmed by means of methylation and NMR spectroscopy analyses; the latter diad has been scarcely reported. The first extracts from tetrasporic plants rendered a pure lambda-carrageenan with considerable yield, which confers this species promising commercial applications. In some cystocarpic and tetrasporic extracts alpha-glucose was also found and assigned to floridean starch by 1H-13C HSQC NMR spectroscopy.
Keywords: iridaea cordata; cystocarpic; tetrasporic; carrageenan; agaran